Exploring Dawet Ayu Banjarnegara as Local Wisdom in Primary School: Integrating Cultural Education Through Local Content Learning - Farras Nafalya Atha Nugroho; Deni Setiawan (JETL (Journal of Education, Teaching and Learning), 2025)
Globalization has influenced students' consumption patterns, leading to a preference for soft drinks over traditional beverages such as dawet ayu. As a result, students often consume dawet ayu without understanding its cultural significance, production process, or historical context rooted in local wisdom. This study aims to analyze the form, role, and urgency of integrating Dawet Ayu Banjarnegara as local content in education, focusing on its cultural value, economic potential, and relevance in entrepreneurship. A qualitative research approach was employed, utilizing triangulation techniques to ensure data validity, and analyzed through the Miles and Huberman model. The findings reveal that educational efforts involving dawet ayu—through careful planning, implementation, and evaluation—can significantly enhance student engagement and learning outcomes in local content education. Moreover, this integration is vital as it supports the preservation of cultural heritage, strengthens economic awareness, fosters entrepreneurial spirit, and cultivates a sense of national identity among students.